Perceived Patient Safety Competence of Baccalaureate Nursing Students: A Descriptive Comparative Study - Lisa M. Rebeschi PhD, MSN, RN, CNE (SAGE Publishing, 2020)
Introduction Patient safety is an issue of utmost concern within health care. An interrelated approach between nursing education and practice is needed. For more than a decade, nursing education programs have responded to calls for curricular reform, integrating strategies to prepare graduates for safe nursing practice. Objectives The purpose of the descriptive study was to examine self-perceived safety competencies among baccalaureate (BSN) nursing students at end of program ( n  = 72) using the Health Professional Education in Patient Safety Survey. In addition to the objective of describing self-perceived safety competencies of BSN students, another objective was to investigate any significant differences in self-perceived competencies between traditional 4-year and accelerated 12-month program students. Methods A descriptive comparative design was used with a purposive sample of baccalaureate nursing students from both traditional and accelerated second-degree programs at a comprehensive university in the Northeast. Results Students rated self-confidence with patient safety learned in the clinical environment higher than within the classroom setting. Overall, students reported a high level of self-confidence within each of the seven patient safety dimensions with knowledge gained from the clinical setting higher than knowledge gained from the classroom setting. Paired t -test analyses revealed statistically significant differences ( p  < .05) between self-confidence gained in classroom and clinical environments with communicating effectively and managing safety risks. Independent t -test analyses revealed accelerated students reported lower self-confidence than traditional students, with statistically significant differences ( p  < .05) in dimensions of culture of safety, working in teams, managing safety risks, and disclosing adverse events/close calls. Conclusion In most patient safety dimensions, students felt confident with their competencies within each of the dimensions of patient safety. Results also revealed that accelerated second-degree students report lower confidence with their knowledge of patient safety gained from classroom and clinical settings. Nursing programs must continue to emphasize a culture of safety within the nursing curriculum.